Recent advances in lithium-sulfur batteries using biomass-derived carbons as sulfur host. (February 2022) - Benítez, Almudena; Amaro-Gahete, Juan; Chien, Yu-Chuan; Caballero, Álvaro; Morales, Julián; Brandell, Daniel
Abstract: While biomass waste is generated in abundance, these materials and their production processes are generally environmentally friendly, low cost, non-hazardous and easily scalable. These advantages position biomass materials as excellent candidates to solve problems of environmental pollution, primarily by substitution of less sustainable counterparts. This also applies to energy storage systems such as batteries, where several components have large environmental impacts. Lithium–Sulfur batteries have, in this context, been extensively researched to cope with the growing energy needs, and are expected to foresee a growing commercialization. Specifically, advances in the use of renewable cathode materials for Li–S batteries is a field that has been widely addressed in recent years, with carbonaceous materials (C) and/or activated carbons (AC), obtained from biomass, being intensively studied. We here reviewed this field through a classification and discussion of carbonaceous materials from natural waste according to the type of biomass: (1) woody, (2) herbaceous and agricultural, (3) aquatic, (4) animal and human, and (5) contaminated and industrial biomass waste materials. In addition, all porous carbons or activated carbons used as sulfur hosts have been exhaustively evaluated in terms of origin, synthesis parameters, physical properties, and electrochemical performance in Li–S batteries. The purpose is to provide a general description of the progress in the preparation of carbons from biomass resources, examine the textural and electrochemical properties of these materials focusing on the last decade, and also to present an outlook for future research in this developing area. Highlights: The use of biomass and biowaste in Li-S batteries is reviewed. Carbonaceous and activated carbons are discussed as sulfur hosts. Woody, agricultural, aquatic, animal and industrial biomass waste is evaluated. Critical parameters are defined for further progress in the field.